If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 29 + -1v = 13 Solving 29 + -1v = 13 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-29' to each side of the equation. 29 + -29 + -1v = 13 + -29 Combine like terms: 29 + -29 = 0 0 + -1v = 13 + -29 -1v = 13 + -29 Combine like terms: 13 + -29 = -16 -1v = -16 Divide each side by '-1'. v = 16 Simplifying v = 16
| 56x^2+168x+112=0 | | 15/5+x=20 | | Factorizex^2+12x+9=0 | | 5x+5-7x=12x+10x-10 | | x+5=3x+25 | | -1y+7=-1(17+y) | | x+y=67 | | 3x-3(2-2x)=8 | | 6x+14=-40-3x | | 3x+5y=2.37 | | 2x+3(4+2x)=8 | | 3z-8=z-10 | | 29+v=13 | | -3m+6=12 | | 8+32-36-(-7)= | | f(x)=3x^2+4x-4 | | -64=-16x | | -x+13=x-13 | | 8+2(16-36)-(-7)= | | 6x/-2x/21=25/21 | | -5+-7-(-4)= | | 2+y=-7+2 | | x+4=105x-104 | | -4a=-28 | | u^2-12u+17=0 | | -5x+3(6x+-16)=191 | | -4y+42=-6+2y | | 0.4x-0.7+0.3x=7 | | 4(6.25)+3x=34.60 | | 6-5-3(2)=8 | | m^4+7m^2=0 | | 3u^2-48=0 |